Healthy pediatric platelets are moderately hyporeactive in comparison with adults' platelets. (4th July 2022) - Ponomarenko, Evgeniya A.; Ignatova, Anastasia A.; Polokhov, Dmitrii M.; Khismatullina, Rimma D.; Kurilo, Darja S.; Shcherbina, Anna; Zharkov, Pavel A.; Maschan, Alexey A.; Novichkova, Galina A.; Panteleev, Mikhail A.
Abstract: Studies on platelet function in children older than neonatal period are few and their results are controversial. The pediatric platelets were alternatively reported to be more active or less active than adults' ones. We compared platelet function in the several age groups of children to adults and evaluated the age when platelet function reaches the adults' status. The study included 76 healthy children and 49 healthy adult volunteers. Types of platelet activation used included: collagen-related peptide (CRP) and PAR-1 activating peptide SFLLRN; SFLLRN, PAR-4 activating peptide AYPGKF and adenosine diphosphate (ADP); ADP. The parameters determined included forward (FSC) and side scatter (SSC), CD42b, CD61, CD62P, PAC-1, annexin V binding and mepacrine release levels. Resting pediatric platelets were similar to adults' platelets except for 1.2-fold decreased FSC and dense granules volume in youngest children, and 2.5-fold increased annexin V level in children aged 1–10 years. After CRP+SFLLRN stimulation, pediatric platelets had a 1.2-fold lower alpha- and 1.1-fold lower dense granule release than adults. For SFLLRN+AYPGKF+ADP stimulation, this was observed only for youngest children. The response to ADP stimulation was identical for pediatric platelets and adults. Pediatric platelets have lower granular release than adults' platelets, which persists until the age of 18.